2021
DOI: 10.1007/s11368-021-02968-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polycyclic aromatic hydrocarbons (PAHs) in the bottom sediments of a dam reservoir, their interaction with organic matter and risk to benthic fauna

Abstract: Purpose The aims of the study were to investigate the interaction between fractions of organic matter and polycyclic aromatic hydrocarbons (PAHs) in bottom sediments and to use mussels as passive biomonitors and consensus-based sediment quality guidelines for ecological risk assessment in sediments. Methods Bottom sediment samples were taken from 46 points located in the Rożnów reservoir (Poland). The sediment organic matter (SOM) characteristics included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 50 publications
0
3
1
Order By: Relevance
“…Although the values for individual PAHs immediately following the fire were elevated, they were still significantly lower than those in other wildfire studies (Table 3) and studies from industrial and urbanised locations across the globe generally, and across Canada specifically (see Marvin et al 2021). Baran et al (2021) focused on a range of organic matter fractions and found that there was a positive correlation between total organic carbon (TOC) and ƩPAHs in bottom sediments in the Rożnów reservoir in Poland, and for dissolved organic carbon and fulvic acid carbon there was a significant relationship between ƩPAHs and 2-3-ring compounds. In the context of the work presented here, this finding is of particular note because of the dominance of 2-3 ring PAHs in both soils and sediments.…”
Section: Discussioncontrasting
confidence: 58%
“…Although the values for individual PAHs immediately following the fire were elevated, they were still significantly lower than those in other wildfire studies (Table 3) and studies from industrial and urbanised locations across the globe generally, and across Canada specifically (see Marvin et al 2021). Baran et al (2021) focused on a range of organic matter fractions and found that there was a positive correlation between total organic carbon (TOC) and ƩPAHs in bottom sediments in the Rożnów reservoir in Poland, and for dissolved organic carbon and fulvic acid carbon there was a significant relationship between ƩPAHs and 2-3-ring compounds. In the context of the work presented here, this finding is of particular note because of the dominance of 2-3 ring PAHs in both soils and sediments.…”
Section: Discussioncontrasting
confidence: 58%
“…According to reports, fish are the most susceptible aquatic organisms for detecting contaminants and pollution in an aquatic environment; hence, they have been used for environmental monitoring of contaminants in rivers ( Cui et al, 2016 ; Olayinka et al, 2019 ; Pang et al, 2021 ; Ciucure et al, 2023 ). Arising from their capacity to bio-accumulate in biota, persist in the environment, having mutagenic and carcinogenic potencies in man, the US EPA has banned some PAHs, hence the interest of all stakeholders especially the researchers for many years ( US EPA, 1993 ; US EPA, 2001 ; Orecchio and Papuzza, 2009 ; Lawal, 2017 ; Gao et al, 2018 ; Baran et al, 2021 ; Cui et al, 2023 ). Several researchers have analyzed, characterized concentrations, and carried out health implications of POPs in which PAHs a member of that group in the past decades across the globe ( Lau et al, 2010 ; Yu et al, 2014 ; Li et al, 2015 ; Wang et al, 2017 ; Gao et al, 2018 ; Ekere et al, 2019 ; Usese et al, 2021 ; Cui et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…[6]. PAHs exhibit semi-volatility, long-term persistence and bioaccumulation of persistent organic pollutants and widely occur in a variety of environmental media [7][8]. Research has indicated that the environmental behavior and bioavailability of PAHs are strongly affected by BC [9].…”
Section: Introductionmentioning
confidence: 99%